Research on Work Values in a Changing Economic and Social Context. Issue 1 (March 2019) - Gallie, Duncan
This article examines the agenda of research on work values that has been developing since the late 1960s. It distinguishes four phases, which successively broadened the scope of research on work values. The first phase focused on the likely impact of economic development and rising incomes on work values. The second interrogated the role of work values for those experiencing unemployment. The third extended the focus to gendered work values related to women's increasing participation in the labor market. Finally, there has been increased interest in the strength of role attachment to a job and organization. In each area of research, the growth over time of cross-national comparative studies has revealed variations in work values across countries that point to the importance of understanding differences in institutional structures and cultural values.